Design and Validation of a Stairmand Cyclone for Partial Filtering of Particulate Material (Docentes 2.0 Journal, 2021)
Particulate materials include solids or liquids or a mixture of them at micrometer scales. These particles can be harmful to the environment and are associated with some human health problems, mainly due to their size. Because of this situation, technologies have been created for their mitigation, such as cyclones. This technology takes advantage of the kinetic energy of the contaminated flow movement to perform a mechanical separation, so they are implemented in various industrial applications such as pre-cleaners of liquids or gases. This research was aimed to design a high-efficiency Stairmand type cyclone for the separation of solid particles in a gaseous flow, with an efficiency of 80%, based on a study problem, where the initial parameters are known together with the variables involved in the system. The methodological process employed for this research focused on a descriptive-correlational study, following the following steps: 1) classification of variables for theoretical calculation, three-dimensional design with simulation analysis,  2) determination of theoretical geometric parameters,  3) cyclone design and modeling in Solidworks® software,  4) theoretical calculation of collection efficiency,  5) collection efficiency analysis with Solidworks® Flow Simulation from simulation results.  Together with the simulation results. The theoretical results showed a coincidence with an error of less than 1%, demonstrating the hypothesis put forward in this research.
Keywords: Design; validation; Stairmand cyclone; partial filtering